2013
DOI: 10.1371/journal.pone.0079863
|View full text |Cite
|
Sign up to set email alerts
|

Ran GTPase-Activating Protein 1 Is a Therapeutic Target in Diffuse Large B-Cell Lymphoma

Abstract: Lymphoma-specific biomarkers contribute to therapeutic strategies and the study of tumorigenesis. Diffuse large B-cell lymphoma (DLBCL) is the most common type of malignant lymphoma. However, only 50% of patients experience long-term survival after current treatment; therefore, developing novel therapeutic strategies is warranted. Comparative proteomic analysis of two DLBCL lines with a B-lymphoblastoid cell line (LCL) showed differential expression of Ran GTPase-activating protein 1 (RanGAP1) between them, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Consistent with this, four key nuclear transport factors, including CRM1, RanGAP1, Ran and RanBP1, are overexpressed in metastatic melanomas compared to primary melanomas and melanocytic nevi [ 63 ]. Further, RanGAP1 has been found as a potential marker and therapeutic target for aggressive B-cell lymphoma, especially diffuse large B-cell lymphoma (DLBCL) [ 73 ]. Because the primarily localization of RanGAP1 in the cytoplasm and at the NPC is required for efficient nuclear transport especially in cancer cells, targeting CRM1 with small-molecule inhibitors in certain types of cancers with overexpression of RanGAP1 and/or CRM1 might be a promising strategy for therapeutic treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, four key nuclear transport factors, including CRM1, RanGAP1, Ran and RanBP1, are overexpressed in metastatic melanomas compared to primary melanomas and melanocytic nevi [ 63 ]. Further, RanGAP1 has been found as a potential marker and therapeutic target for aggressive B-cell lymphoma, especially diffuse large B-cell lymphoma (DLBCL) [ 73 ]. Because the primarily localization of RanGAP1 in the cytoplasm and at the NPC is required for efficient nuclear transport especially in cancer cells, targeting CRM1 with small-molecule inhibitors in certain types of cancers with overexpression of RanGAP1 and/or CRM1 might be a promising strategy for therapeutic treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…OCI-Ly3 and U2932 cells (originally purchased from Deutsche Sammlung von Mikroorganismen und Zellkulturen (DSMZ), Germany) were gifts from Dr. Chun-Yu Liu (Taipei Veterans General Hospital, Taiwan). SU-DHL-5 and HT cell lines were obtained from Dr. Kung-Chao Chang (National Cheng Kung University, Taiwan) and have been described previously 45 . The OEC-M1 human head and neck cancer cell line was provided by Dr. Kuo-Wei Chang (National Yang-Ming University of Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…We found that RNAi-mediated RanGAP reduction induces cell cycle arrest of undifferentiated CPCs, where endogenous Cdc6 is localized to the cytoplasm. It has previously been reported that RNAimediated down-regulation of RanGAP expression induces cell cycle arrest in human coronary artery smooth muscle cells and B-cell lymphoma cells (Chang et al 2013;Vorpahl et al 2014). Thus, we assume that forced reduction in RanGAP levels in proliferative cells induces cell cycle arrest, at least in part, due to impeded nuclear import of Cdc6.…”
Section: Discussionmentioning
confidence: 84%
“…It has previously been reported that RNAi‐mediated down‐regulation of RanGAP expression induces cell cycle arrest in human coronary artery smooth muscle cells and B‐cell lymphoma cells (Chang et al . ; Vorpahl et al . ).…”
Section: Discussionmentioning
confidence: 99%